PERJALANAN PASCAKOLONIAL DALAM TAMASYA DENGAN PERAHU BUGIS KARYA ZUBER USMAN - Christopher Allen Woodrich (Universitas Sanata Dharma, 2013)
During the colonial period journeys were acts of conquest, attempts to create order by limiting the world through which one passed by what could be seen and charted. Postcolonial journeys, however, seek the freedom offered by a delimited environment and use it as a site of resistance against an oppressive power. An early Indonesian example, although by no means the earliest, can be found in ZuberUsmans Tamasya dengan Perahu Bugis. Written in 1943, during the Japanese occupation, the short story details a mans trip from Surabaya to Makassar. Although it remains presented in colonial terms, the story offers postcolonial techniques, including an emphasis on the journey itself and the possibility of an unending journey, rendering the colonial techniques used a replay of the colonial journey. Through this, the story succeeds in sending a message that the Japanese overlords were unable to completely subjugate the Indonesian people through colonisation: chaos is still possible.Key words : Zuber Usman, Pascakolonial, Perjalanan pascakolonial